Comparison of two bone markers with growth evolution in 74 girls with central precocious puberty - Vincent, Audrey (BMC Pediatr, 2018)
BACKGROUND: The bone markers bone alkaline phosphatase (BAP) and C-terminal telopeptide of type I collagen crosslinks (CTX) are correlated with growth rate during normal puberty. The objective of this study was to evaluate the relationship between the serum concentrations of BAP and CTX and growth evolution in girls with idiopathic central precocious puberty (CPP) to help predict adult height. METHODS: A retrospective single-center study was conducted in 74 girls with CPP for whom a serum sample at initial evaluation was available to retrospectively measure BAP and CTX concentrations; 66.2% of them were untreated. RESULTS: The serum BAP concentrations showed significant positive correlations with height in standard deviations (SDS) at the initial evaluation (n = 62; r = 0.31; p = 0.015) and with the difference between bone and chronological ages (n = 61; r = 0.39; p = 0.002). BAP was also positively correlated with adult height as measured in both cm and SDS in untreated patients (n = 19; r = 0.58; p = 0.009). The serum CTX concentrations showed significant positive correlations with growth rate the year before the initial evaluation as measured in both cm and SDS (n = 65; r = 0.34; p = 0.006). CONCLUSIONS: This study revealed significant correlations of serum BAP and CTX concentrations with growth evolution in girls with CPP. The high positive correlation between serum BAP and adult height in untreated girls suggests that BAP can possibly be used to optimize models of adult height prediction in girls with CPP.